First report of Neopestalotiopsis clavispora causing leaf blight on Schefflera octophylla in China - Lin, Qiaoling; He, Junxian; Chen, Kejing; Chen, Xintong (Plant disease, 2025)
Schefflera octophylla is widely cultivated in South China due to its high ornamental and economic value. In April 2022, a leaf disease on S. octophylla was observed in Zhanjiang (21.20° N, 110.41°E), China. Disease incidence and severity were 15% and 20% (n = 100 investigated plants), respectively. Symptoms on leaves primarily appeared as small light gray spots, then enlarged and coalesced into regular or irregular light gray necrotic lesions with dark margins. Ten symptomatic leaves from 10 plants were collected. Small pieces of tissue (4 × 4 mm) were cut from lesion borders and were surfaced disinfected in 75% ethanol for 30 s, followed by 1 min in 1% NaClO, rinsed three times with sterile water, plated on potato dextrose agar (PDA), and incubated at 28°C. After 5 days, fifteen morphologically similar fungal isolates were obtained from all 10 leaf samples and three representative strains (YZM-1, YZM-2, and YZM-3) were used for morphological and molecular characterization. Colonies were white with cottony aerial mycelium. After 10 days, black viscous acervuli were scattered on the colony surface. Conidia were clavate to fusiform, four-septate, straight or slightly curved, and measured 17.57-25.70 × 4.53-6.80 μm (mean 23.13 × 5.14 μm) in size (n = 50). Basal and apical cells were colorless while the three medium cells were dark brown and versicolor. Conidia had a single basal appendage (4.5 to 5.5 μm long; n = 50) and two or three apical appendages (18.2 to 33.5 μm long; n = 50). These morphological characteristics were consistent with the description of Neopestalotiopsis clavispora (Maharachchikumbura et al. 2012). For further identification, genomic DNA was extracted by the 2% CTAB method (Lu et al. 2012). The internal transcribed spacer (ITS) region and β-tubulin 2 (tub2) and translation elongation factor 1-alpha (tef1α) genes were amplified using the primers ITS1/ITS4, T1/Bt-2b, and EF1-728F/EF-2 respectively (Maharachchikumbura et al. 2012). The ITS (OM721785-87), tub2 (OQ130413-15) and tef1α (OM810189-91) sequences were 99.38%, 99.33%, and 99.17% identical to the N. clavispora type strain MFLUCC12-0281 (accession nos. JX398979, JX399014, and JX399045, respectively). A phylogenetic tree was generated using the concatenated sequences of ITS, tub2, and tef1α. All three isolates clustered with N. clavispora strains including the type MFLUCC12-0281. For pathogenicity tests, 2-year-old S. octophylla plants (n=10) were sprayed with a conidial suspension (105 conidia/ml) on the surface of wounded leaves. Mock-inoculated controls (n=10) were sprayed with sterile distilled water. All plants were wrapped in polyethylene bags for 24 h and incubated at 28°C in a growth chamber at 90% relative humidity. After 10 days, all inoculated leaves showed similar symptoms to those observed in the field, whereas control leaves were asymptomatic. N. clavispora was re-isolated from the lesions and the identity of the fungus was confirmed based on morphology and molecular characterization. The pathogenicity test was repeated three times with similar results. N. clavispora has been reported to cause diseases in a broad range of hosts (Chen et al. 2018; Borrero et al. 2018), but not in S. octophylla. This is the first report of N. clavispora causing leaf blight on S. octophylla in China. Damage caused by N. clavispora could cause significant economic losses if not managed. More research is needed to better understand this disease and establish control strategies.